AN ANALYSIS OF MIRIN D ZANGA 12DA NOVEL ACCORDING TO SARA MILLS' FEMINIST STYLISTIC MODEL - Salih , Aveen; Abdulrahman, Hussein (Humanities Journal of University of Zakho, 2025)
Feminist stylistics’ is a modern and critical approach that integrates linguistics and feminist criticism to examine how societal structures influence the language and style of literary texts. It also explores stylistic differences between male and female writers. This study applies Sara Mills' feminist stylistic framework to analyze the novel Mirin di Zenga 12 da (Death at the 12th Bell), marking the first application of this model to the text within Kurdish literary research. While feminist criticism has been explored in Kurdish studies, this specific interpretative approach remains underexamined. Therefore, this research introduces a new perspective in the study of feminist stylistics. It is anticipated that the author employs a language distinctive to female writers in this novel, differing from the stylistic choices of male writers. This distinction makes the text particularly relevant for analysis through a feminist lens. The study challenges traditional literary methodologies by examining how linguistic features reflect feminist ideas. In other words, this approach reveals ideological biases within the text by deconstructing its linguistic structure. The findings suggest that although the author was largely able to maintain a feminine linguistic style in her text, she was not entirely free from the influence of dominant masculine language. This may be due to the impact of prevailing societal thought, beliefs, and masculine values that have affect the author.